1997
DOI: 10.1079/pns19970057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic nitrogen metabolism in ruminants

Abstract: As befits its anatomical position between the sites of nutrient absorption and deposition the liver provides the metabolic hub of the body. Although the present review is confined to the regulation of N substrates it must not be forgotten that both lipid and carbohydrate metabolism are important and interactive components of hepatic function. Furthermore, hepatic production of insulin-like-growth-factor (1GF)-1 and partial removal of glucagon and insulin play an important part in regulation of peripheral endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 56 publications
0
31
1
Order By: Relevance
“…Bertilsson and Murphy (2003) showed that, whilst clover and clover-grass mixture silages gave higher voluntary DMI than grass silage, the resulting increase in N intake led to reductions in the efficiency of conversion of dietary N to milk N. Noticeable was the low protein utilization for the fresh forage diets compared with the legume-supplemented silage diets, too, as the first resulted in a particularly high N load. Both, plasma and milk urea are indicators of metabolic N excess as it is synthesized in the liver not only from amino acid catabolism in the liver but, in the situation of excess, mainly from ammonia produced in the rumen (Lobley and Milano, 1997). Hence, when no excessive amino acid supply is taking place, urea reflects the extent of CP degradation in the rumen (Broderick and Clayton, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Bertilsson and Murphy (2003) showed that, whilst clover and clover-grass mixture silages gave higher voluntary DMI than grass silage, the resulting increase in N intake led to reductions in the efficiency of conversion of dietary N to milk N. Noticeable was the low protein utilization for the fresh forage diets compared with the legume-supplemented silage diets, too, as the first resulted in a particularly high N load. Both, plasma and milk urea are indicators of metabolic N excess as it is synthesized in the liver not only from amino acid catabolism in the liver but, in the situation of excess, mainly from ammonia produced in the rumen (Lobley and Milano, 1997). Hence, when no excessive amino acid supply is taking place, urea reflects the extent of CP degradation in the rumen (Broderick and Clayton, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, data for hepatic removal of AA are expressed as a fraction of the amount absorbed and, indeed, such extractions can be high. For example, absorbed histidine and phenylalanine can be totally removed across the liver in non-growing sheep (Lobley and Milano 1997). In practice, however, the liver is presented not with just absorbed AA but a mixture that also includes re-circulated AA (derived from recently absorbed material that bypassed the liver, plus that released by breakdown of tissue proteins).…”
Section: Hepatic Catabolismmentioning
confidence: 99%
“…
Metabolism in the gastrointestinal tract ) and liver (Lobley & Milano, 1997) has been shown to be important in determining the amount and pattern of amino acids (AA) available post-hepatically for mammary gland utilization as well as for muscle, skin and, indeed, the gastrointestinal tract. High rates of metabolism by the non-mammary tissues have been suggested as one reason for the low efficiency (approximately 20 %) of conversion of dietary N into milk protein .
…”
mentioning
confidence: 99%